Nondestructive measurement of surface roguhness of 3D printed sample - Goh, Shermaine Xin Mei (Nanyang Technological University, 2021)
3D printing using EBM technology is commonly used in many industries such as aerospace, manufacturing, medical and robotics, as it reduces cost and increases productivity. However, the surface finishing of the printed product is like sand casting and requires post-processing, such as polishing. It is important for the surface finishing to be monitored and controlled during the polishing process. The level of surface finishing depends on the function of the parts, as different industries require a different level of finishing. Since 3D printing allows complex geometries to be printed, there could be internal surface roughness that cannot be measured by a standard Profilometer. To prevent the damaging of the parts, NDT is usually used to measure surface roughness. This report presents an ultrasonic surface roughness measurement method for online monitoring of the internal surface polishing process. The method uses a single element transducer as both the transmitter and receiver. The experiments were conducted to compare the ultrasonic test results to the Profilometer for validation of the proposed method. Results from the ultrasonic tests show great correlations with those obtained by a stylus Profilometer. Finally, a fixture is designed for the online monitoring of internal surface polishing.